Government Communication of the Regional House of Representatives in the Process of Formulating Regional Regulations in Indonesia - Ilham Gemiharto (Ikatan Sarjana Komunikasi Indonesia, 2023)
The Regional House of Representatives (DPRD) is a legislative body representing the votes of the vast majority of the populace, and its members are answerable to it. Legislature members have duties, responsibilities, and rights that must be carried out at work. However, DPRD encounters several issues that make carrying out these duties difficult. This study's objectives include examining the Regional House of Representatives Government Communication regarding the formulation of regional regulations in Indonesia, the challenges faced by DPRD members in converting regional regulations draft (Raperda) into regional regulations (Perda), and the DPRD's model for formulating policy in Indonesia. In this work, qualitative research is combined with an empirical legal methodology. Under natural circumstances, data were gathered through observation, in-depth interviews, and documentation studies. This study concludes that the government communication of the Raperda formulation in the DKI Jakarta Provincial DPRD follows the Prudential Principle or is done with extreme caution. The DPRD's use of the precautionary principle can be compared to Dunn's idea of forecasting, namely projection. Discussions around developing proposed regional rules almost always involve challenges and issues. Since political influence is crucial, all efforts will be made in this vein.